Supporting infants and parents in the perinatal period (SIPP): Co-creating an improved journey - Tami Benzaken; Francesca Siracusa; Michelle D’Souza; Radhika Gulati; Esta Orchard; Alexandra Lemaigre; Clare Andrews; Mitch Blair (PLoS ONE, 2025)
There has been a 70% increase in infant A&E attendance across England in the last decade, much of it non-urgent, highlighting the need to improve parental confidence and services for infant care. A multidisciplinary group of healthcare professionals was established with the aim of understanding and evaluating the support given to new parents in the early postnatal period. We recruited parents and caregivers of infants born in a large district hospital. Participants were recruited in the postnatal ward and neonatal unit. Participants were offered face-to-face or virtual interviews with an interpreter where required. Seventeen semi-structured interviews were conducted between February and September 2022 (16 virtual, 1 face-to-face). Thematic content analysis was used to manually identify codes and refined to develop a common coding framework which was used to identify final themes and subthemes. Following the initial set of interviews, a focus group with 12 different participants was held to validate the themes. Two main themes were identified: (1) service access, continuity, consistency, and personalisation of care are highly valued, and (2) preparation and support during transition is important and individual. Within theme 1, we identified facilitators (health literacy, consistent messaging, telephone line), barriers (staff shortages, communication between healthcare workers, discrimination), and person-centred care as sub-themes. In theme 2, participants highlighted the importance of their expectations of normal, support from family and friends, and experiences using applications and social media. Effective support and care in the postnatal period are vital for ensuring and promoting the health and wellbeing of mothers and their babies. These findings were presented to local maternity services and service users by the research team, resulting in local service improvements.